Perempuan Dalam Pemenuhan Ekonomi Keluarga Di Masa Pandemi Corona: Studi Kasus Pada Ibu Rumah Tangga Di Desa Banua Kecamatan Malunda Kabupaten Majene - Ratnah Rahman; Nurlinda Angraeni (SOSIORELIGIUS, 2020)
This study aims to explain the role of women in meeting economic needs during the corona pandemic. This research is motivated by the difficulties experienced by some communities in meeting the needs of families caused by the emergence of the corona pandemic. This research was conducted using qualitative method, data obtained through observation, interview, and documentation. Field phenomena are analyzed using sociological and phenomenological approaches. The results showed that First, the role of women in meeting needs during the pandemic contributed in increasing family income and improving family welfare during the pandemic. Second, the purpose of working women is to earn wages that are used to increase income in order to meet the needs that relieve the burden of husbands. The income earned from working women is used to meet needs such as children's education, adequate kitchen needs and community.